(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2024)
The aim of the article is to analyze and evaluate customer satisfaction in the logistics service provided by a company operating on the express courier market in the Koszalin district. The publication presents the courier services market in Poland. The research methods used in the article are the analysis of literature and Internet sources and the diagnostic survey method (the research took place in Koszalin County, in 2021-2022), as well as the calculation of the CSI index – customer satisfaction level. The research result clearly showed that DHL Koszalin customers are satisfied with the services provided. However, one more important factor for respondents when choosing the DHL courier service was price.